In Vitro Regeneration of Sambong (Blumea balsamifera Linn.) - Soriano, Thelma L. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2009)
A procedure for the in vitro culture of sambong (Blumea balsamifera Linn.) which utilizes terminal shoot was developed. Shoot tips cultured in Murashige and Skoog (MS) medium containing 1.0 mg L -1 benzyl adenine (BA) initiated and regenerated shoot cultures. Roots were formed in shoots grown in Murashige and Skoog medium supplemented with 0.5-1.0 mg L -1 naphthalene acetic acid (NAA). Exposure to high humidity for the first 2 wk and equal proportions of sterile sand, compost and coir dust as potting mix favored the development of sambong plants. Aside from in vitro culture, very young shoot cuttings from in vitro-derived sambong plants could be used for propagation. Furthermore, the mineral content (ash, crude fat, calcium, magnesium and iron) of sambong leaves derived from tissue culture (in vitro) and from the field (in vivo) were not significantly different from one another. However, in vitro-derived sambong leaves contained significantly greater amount of crude protein and significantly lower amount of carbohydrates and phosphorus than in vivo-derived leaves.